2010
DOI: 10.1371/journal.pone.0009010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Physiological Activation of Osmosensitive Gene Expression Mimics Transcriptional Signatures of Pathogen Infection in C. elegans

Abstract: The soil-dwelling nematode C. elegans is a powerful system for comparative molecular analyses of environmental stress response mechanisms. Infection of worms with bacterial and fungal pathogens causes the activation of well-characterized innate immune transcriptional programs in pathogen-exposed hypodermal and intestinal tissues. However, the pathophysiological events that drive such transcriptional responses are not understood. Here, we show that infection-activated transcriptional responses are, in large par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
112
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(124 citation statements)
references
References 53 publications
(91 reference statements)
12
112
0
Order By: Relevance
“…1C). Whole genome cDNA microarray studies have confirmed that, in addition to gpdh-1, mutations in osr-1, osm-7, osm-8, and osm-11 constitutively activate many genes that are responsive to high osmolarity, indicating that they mimic signaling changes that normally occur with high osmolarity (99).…”
Section: R180 Salt and Water Homeostasis In C Elegansmentioning
confidence: 91%
See 3 more Smart Citations
“…1C). Whole genome cDNA microarray studies have confirmed that, in addition to gpdh-1, mutations in osr-1, osm-7, osm-8, and osm-11 constitutively activate many genes that are responsive to high osmolarity, indicating that they mimic signaling changes that normally occur with high osmolarity (99).…”
Section: R180 Salt and Water Homeostasis In C Elegansmentioning
confidence: 91%
“…A major remaining question is the identity of the inducible transcription factor that transactivates gpdh-1 and other osmosensitive genes (99). In many mammalian cells, the rel-type transcription factor NFAT5/TonEBP accumulates in the nucleus in response to high osmolarity and orchestrates adaptive gene expression (81).…”
Section: R180 Salt and Water Homeostasis In C Elegansmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7] Importantly, several hyperosmotic stressresistant C. elegans mutants display heightened glycerol levels due to constitutive activation of gpdh-1 and subsequent glycerol accumulation. [8][9][10][11][12] Although the use of glycerol in invertebrates to survive hyperosmotic stress is widely accepted, what fuels the rapid glycerol production upon hyperosmotic stress exposure has not been clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%